2014
DOI: 10.1155/2014/291458
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolidase Activity and Oxidative Stress in Diabetic Nephropathy and End Stage Renal Disease: A Correlative Study with Glucose and Creatinine

Abstract: Association of oxidative stress and serum prolidase activity (SPA) has been reported in many chronic diseases. The study was aimed at evaluating the correlation of glucose and creatinine to SPA and oxidative stress in patients with diabetic nephropathy (DN) and end stage renal disease (ESRD) concerned with T2DM. 50 healthy volunteers, 50 patients with T2DM, 86 patients with DN, and 43 patients with ESRD were considered as control-1, control-2, case-1, and case-2, respectively. Blood glucose, creatinine, SPA, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
16
0
2
Order By: Relevance
“…In the present study, the DM group had higher levels of oxidative marker MDA and lower levels of antioxidative marker T-SOD. This was consistent with the studies that reported increased oxidative activity in diabetic subjects (34,35). There is increasing evidence from pre-clinical and clinical studies, which suggests that antioxidant agents have potential ameliorative effects on diabetic complications, including DN (17,36,37).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the DM group had higher levels of oxidative marker MDA and lower levels of antioxidative marker T-SOD. This was consistent with the studies that reported increased oxidative activity in diabetic subjects (34,35). There is increasing evidence from pre-clinical and clinical studies, which suggests that antioxidant agents have potential ameliorative effects on diabetic complications, including DN (17,36,37).…”
Section: Discussionsupporting
confidence: 90%
“…Verma et al 20 reported that prolidase activity, TOS, and OSI were significantly higher in diabetic nephropathy and end-stage renal disease group than in controls, whereas TAS were significantly lower. We also found in this study that prolidase activity and TOS levels were significantly lower and OSI levels were significantly higher in patients with COPD than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…The increased oxidative stress maintained by different antioxidant system (ascorbic acid, vitamin-E, SOD and so forth) and this antioxidants status altered in different uncontrolled disease condition [29][30][31][32]. Ascorbic acid, an antioxidant, has negative correlation with the major depression is a finding well-established [33].…”
Section: Discussionmentioning
confidence: 99%